The African Union's sanction regime : theoretical analysis of the coercive mechanisms of the african regional integration system - (:unkn) unknown (My University, 2019)
Like other continents, Africa equipped itself with a body in charge of implementing its political and economic ambitions. However, setting up a structure of such magnitude with the appropriate robust instruments to ensure its functioning was an uphill task. The institutional reform of this African regional body in early 2000, by the change of name, was an affirmation of measures sanctioning the non-respect of its rights. Yet, the existence of such norms in the African context was not without difficulties. From the onset of regional construction with the creation of the Organization of African Unity (O.A.U.) in 1963, sanctions were not conceptualized or envisaged in the original texts. The main reason for this shortcoming was that as soon as they were set free from the colonial yoke, African States were not ready to allow themselves to be robbed of their newly won sovereignty gotten through the hard battles for independence. The creation of a continental body in Africa, with coercive powers, was a delicate issue at that time because of this sensitive heritage. Despite such obstacles, the Organisation endeavoured through hardship, to operate and to affirm the power of sanction. Nonetheless, due to the lack of appropriate mechanisms, and other persistent functional shortcomings, the Organization of African Unity was forced to undergo institutional reform. On 9 September 1999 in Syrte, Libya, member States adopted a Declaration on the creation of a new body, the African Union, which replaced the O.A.U in 2002. The institutional reorganization of the regional body opened wide, the door to sanctions. Since then, sanctions figure prominently in the founding texts of this body and are enforced to sanction the non-compliance of States with their obligations, to prohibit coups or other anti-constitutional changes of Government. They focus especially on the establishment of mechanisms for the protection of human rights, plus the principles and ideals of this body
Keywords: African Research